Evaluation of physico-chemical and mechanical properties of MTA-based root canal sealer - Clauber Romagnoli; Klíssia Romero Felizardo; Ricardo Danil Guiraldo; Alcides Gonini Júnior; Renan Hideki Kaneshima; Sandrine Bittencourt Berger; Murilo Baena Lopes (Universidade Estadual de Campinas, 2018)
Aim: The aim of this study was to evaluate and compare the setting times (ST), flow (FW), radiopacity (RP), dimensional stability (DS), solubility (SB), and polymerization stress (PS) of the MTA Fillapex and AH Plus root canal sealers. Methods: The above qualities were tested according to ISO 6876/2001 standardization. The water used in the dimensional stability test was evaluated to verify the presence of released materials. For the photoelastic analysis, 20 photoelastic resin rings were prepared, and the root canal sealers were inserted. After 24 hours, the specimens were analyzed in a Polariscope. Data of the setting times, flow tests, radiopacity, dimensional stability, and solubility tests were submitted to a Kolgomorov-Smirnov test and then to a Student's t-test at the 5% significance level. Results: The data derived from photoelastic analyses were submitted to an ANOVA and Tukey's test with a significance level of 5%. MTA Fillapex and AH Plus complied with ISO 6876/2001. However, there were significant differences (p < 0.05) between the two cements for ST, FW, RP, DS, and SB. MTA Fillapex showed higher FW, SB, and PS when compared with AH Plus. Conclusions: MTA Fillapex and AH Plus complied with ISO 6876/2001 in terms of ST, FW, RP, DS, and SB. MTA Fillapex showed higher PS when compared to AH Plus.